The superoxide dismutase mimetic TEMPOL modulates nicotine-induced hyperlocomotor activity and nicotine-taking behavior in male rats - Kyung Oh Jeon; Jordan T. Yorgason; Lauren Ford; Joel T. Woolley; Seong-Hoon Park; Byoung-Seok Lee; Eun Kyeong Lee; Jaerang Rho; Eun Young Jang (Scientific Reports)
Abstract Reactive oxygen species (ROS) have been implicated in behaviors induced by acute or repeated cocaine or methamphetamine administration in rodents. In the present study, we investigated the involvement of ROS in behavioral changes induced by nicotine administration and dopamine (DA) transmission changes in the nucleus accumbens (NAc) of rats. Rats were given repeated saline or nicotine (0.4 mg/kg) administration once daily for seven days, and the induction of hyperlocomotor activity, and oxidative stress marker expression induced by the increase in ROS production in the NAc were measured on day 7. We also tested the effect of ROS scavengers on repeated nicotine-induced hyperlocomotor activity and nicotine self-administration, and DA levels in the NAc. Repeated nicotine administration induced hyperlocomotor activity and decreased the expression of oxidative stress markers, such as superoxide dismutase-1 and glutathione peroxidase 1/2, by elevating ROS production in the NAc. Pretreatment with the nonspecific ROS scavenger PBN and the superoxide-selective scavenger TEMPOL significantly attenuated nicotine-induced hyperlocomotor activity without impairing motor function in nicotine-naïve rats on day 7. In addition, in intravenous nicotine self-administration study, TEMPOL significantly reduced nicotine-taking behavior without affecting food intake in nicotine-naïve rats. Furthermore, TEMPOL pretreatment prevented nicotine effects on stimulated DA release in the NAc, which was associated with nicotine-induced behavioral changes. Taken together, these findings suggest that increased ROS production in the NAc contributes to the neuropharmacological properties of nicotine.